GEOCHEMICAL MODELS OF METASOMATISM IN ULTRAMAFIC SYSTEMS: SERPENTINIZATION, RODINGITIZATION, AND SEA FLOOR CARBONATE CHIMNEY PRECIPITATION - Palandri J.L.; Reed M.H. (My University, 2004)
In a series of water-rock reaction simulations, we assess the processes of serpentinization of harzburgite and related calcium metasomatism resulting in rodingite-type alteration, and seafloor carbonate chimney precipitation. At temperatures from 25 to 300°C (P = 10 to 100 bar), using either fresh water or seawater, serpentinization simulations produce an assemblage commonly observed in natural systems, dominated by serpentine, magnetite, and brucite. The reacted waters in the simulations show similar trends in composition with decreasing water-rock ratios, becoming hyper-alkaline and strongly reducing, with increased dissolved calcium. At 25°C and w/r less than ∼32, conditions are sufficiently reducing to yield H2 gas, nickel-iron alloy and native copper. Hyperalkalinity results from OH− production by olivine and pyroxene dissolution in the absence of counterbalancing OH− consumption by alteration mineral precipitation except at very high pH; at moderate pH there are no stable calcium minerals and only a small amount of chlorite forms, limited by aluminum, thus allowing Mg2+ and Ca2+ to accumulate in the aqueous phase in exchange for H+. The reducing conditions result from oxidation of ferrous iron in olivine and pyroxene to ferric iron in magnetite. Trace metals are computed to be nearly insoluble below 300°C, except for mercury, for which high pH stabilizes aqueous and gaseous Hg°. In serpentinization by seawater at 300°C, Ag, Au, Pd, and Pt may approach ore-forming concentrations in sulfide complexes. Simulated mixing of the fluid derived from serpentinization with cold seawater produces a mineral assemblage dominated by calcite, similar to recently discovered submarine, ultramafic rock-hosted, carbonate mineral deposits precipitating at hydrothermal vents. Simulated reaction of gabbroic or basaltic rocks with the hyperalkaline calcium- and aluminum-rich fluid produced during serpentinization at 300°C yields rodingite-type mineral assemblages, including grossular, clinozoisite, vesuvianite, prehnite, chlorite, and diopside.